Praktek Tasawuf Pada Thoriqoh Qodiriyyah Naqsyabandiyah di Kelurahan Terjun Kecamatan Medan Marelan - Rohana Rohana (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
This article aims to explore the teachings on Thoriqoh Qodiriyyah Naqsyabandiyyah related to soul purification, through practices taught through the guidance of Mursyid Teachers. Which with Sufism becomes the antidote to solve problems related to the heart. With tarekat as the way. This study discusses specifally about the ways of purification or cleansing of the soul in Thoriqoh Qodiriyyah Naqsyabandiyyah. the result is that in Thoriqoh Qodiriyyah Naqsyabandiyyah there are stages of purification of the soul through the Sufism method, namely tahalli, takhalli, and tajalli.